Identifying cross-species regimens for the treatment of rapid-growing and slow-growing nontuberculous Mycobacterium pulmonary infections - Whittel, Nicholas, author; Slayden, Richard, advisor; Crick, Dean, committee member; Abdo, Zaid, committee member; Wilusz, Jeffrey, committee member; Geiss, Brian, committee member; Tjalkens, Ron, committee member (Colorado State University. Libraries, 2026)
Nontuberculous mycobacteria (NTM), especially Mycobacterium avium and Mycobacterium abscessus, are increasingly significant causes of chronic pulmonary disease. Current treatments are lengthy and often ineffective, with culture conversion often below 60% in refractory patient populations. Due to the close biological relationship between Mycobacterium tuberculosis (TB) and NTM species, TB standard-of-care (SoC) drugs were evaluated for repurposing to develop regimens with activity across diverse NTM pathogens. Comparative genomics using the Distilled Refined Annotation of Metabolism (DRAM) tool demonstrated that bioenergetic pathways, including oxidative phosphorylation and central carbon metabolism, are highly conserved across both slow- and rapid-growing NTM species. This conservation supports targeting mycobacterial bioenergetics as a strategy for cross-species therapeutic development. Drug activity was assessed using in vitro minimum inhibitory concentration (MIC) testing, Raw264.7 macrophage infection assays, and preclinical NTM lung infection models (C57BL/6 for M. avium and NOD.CB17-Prkdcscid/NCrCr for M. abscessus). Efficacy was directly measured as the reduction in lung bacterial count (Δlog10 CFU) compared to untreated controls. Regimens were compared using a multi-metric framework incorporating absolute bacterial reduction, Hedges' g effect size, and the MIC-adjusted clearance index (MACI). Bedaquiline (BDQ) demonstrated the most consistent single-drug activity across intracellular and in vivo models of M. avium and M. abscessus infection. Macrolides, fluoroquinolones, and rifabutin demonstrated comparable in vitro potency, but had variable performance across models. Azithromycin and ofloxacin were also effective and displayed synergy when combined with bedaquiline. Combinations of bedaquiline with azithromycin or ofloxacin produced greater reductions in bacterial burden than monotherapies. A three-drug regimen consisting of bedaquiline, azithromycin, and ofloxacin, consistently ranked among the most effective regimens across both species. The two-drug combinations of bedaquiline-azithromycin and bedaquiline-ofloxacin also functioned as modular backbones that could be pared with additional agents to improve species-specific activity. This study shows that TB SoC drugs can be effectively combined into regimens with activity across multiple NTM species. The identification of both a three-drug regimen with strong cross-species potency and adaptable two-drug backbones provides a framework for developing more effective treatment strategies for NTM pulmonary disease and supports further evaluation of BDQ-anchored regimens in advanced preclinical models.
Keywords: cell models; cross-species regimen; nontuberculous mycobacteria; combination regimen; animal models; drug susceptibility